Sistema de gestión documental para los procesos académicos en la Facultad de Ciencias de la Ingeniería y Aplicadas de la Universidad Técnica de Cotopaxi - Pilapaña Tipan, Leonardo Steve (2022)
The administrative academic processes that are executed within the Faculty of Engineering and Applied Sciences of the Technical University of Cotopaxi generate documentary information that is managed in various platforms such as: Google Drive, Gmail, Classroom, Moodle, among others. Which means that the document management flow is not adequate, together this forces the administrator to have to adapt to third-party applications which do not cover the specific needs of the administrator. In this same context, there is a risk that these platforms may charge for their services, attacking the budget allocated for these areas. Given the existing need to carry out an appropriate document management within the faculty in the administrative academic field, this project seeks to implement a document management system to manage the documentation generated using software development tools and agile practices. In the first instance, a bibliographic review has been carried out to define concepts related to document management, web applications and tools for software development. At the same time, issues related to development methodology and agile practices for research and practical development processes have been addressed. Subsequently, the field investigation has been carried out where meetings have been held with the owner of the system through interviews. This is how, through the use of agile practices, the specification of requirements for the development of the system has been achieved. Lastly, the validation of the results and the project proposal are carried out applying the expert judgment technique where the Cronbach's Alpha coefficient was applied for the analysis of results.